ROLE PLAY FOR TEACHING SPEAKING IN ENGLISH FOR ACCOUNTING - Fitria Nur Hamidah (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2017)
Speaking is one of English skills in teaching and learning process. It is also one of the target of the students to speak in learning English for Specific Purposes especially in English for Accounting. In achieving the target in teaching speaking, it is needed a method which is appropriate in speaking activity when the students practice to speak in the classroom. This study aims to describe the use of role play for teaching speaking especially to the students in English for Accounting. It describes speaking activities by using role play and the benefit of role play for teaching speaking in English for Accounting. Role play can be as an effective method that the ESP lecturer uses in teaching speaking of English for Accounting. It gives students more chances to act and interact with their groups and they bring liveliness and lighten up the atmosphere in speaking class.